= (-1)^2 (d^2/ds^2) laplace(cos(t))

= (d^2/ds^2) (s/(s^2+1))

= (d/ds) [-2s^2(s^2+1)^-2 + (s^2+1)^-1]

= 8s^3/ (s^2+1)^3 - 6s/(s^2+1)^2

thats the answer i got but the answer in the book says (2s^3 - 6s)/ (s^2+1)^3

where did i go wrong?

Printable View

- April 20th 2011, 05:45 PMlinalg123laplace transform(t^2cos(t))=
= (-1)^2 (d^2/ds^2) laplace(cos(t))

= (d^2/ds^2) (s/(s^2+1))

= (d/ds) [-2s^2(s^2+1)^-2 + (s^2+1)^-1]

= 8s^3/ (s^2+1)^3 - 6s/(s^2+1)^2

thats the answer i got but the answer in the book says (2s^3 - 6s)/ (s^2+1)^3

where did i go wrong? - April 20th 2011, 05:58 PMChris L T521
- April 20th 2011, 06:22 PMlinalg123
ughh..duhhh.. thanks